The imago Dei Weltanschauung as narrative motif within the Corinthian correspondence - Kok, Jacobus (Verbum et ecclesia, 2016)
This article reflects on the doctrine of humanity to explore that God created humankind in his image and likeness, and this means that all human beings have an inherent capacity to know the difference between good and bad, and between right and wrong. Thus, all human beings have an innate ability to be ethical, as the God who created them is good, and so becomes the source of their ethics. This article title highlights the interrelationships between identity, ethics, and ethos. These three related analytical categories, within the New Testament, show the necessity for an interdisciplinary approach in treating questions of the origin of humanity. This article incorporates reflections in the studies of anthropology, philosophy, and theology and draws from the writings of Apostle Paul, in his Corinthian Correspondence, as he instructed them on how they ought to relate, and what would be their roles within the broader scope of God's original intention for humanity. In this attempt, he made reference to the anthropological identity of the imago Dei, and he shows that the perfect expression of the imago Dei is Christ Jesus; thus, this is the image they ought to emulate. Therefore, this article investigates The imago Dei weltanschauung as narrative motif within the Corinthian correspondence'.Intradisciplinary and/or interdisciplinary implications: This research gives the perspective of the presupposition of the imago Dei as presented in the New Testament as the framework of understanding ethics, as it appears within the formation of an anthropological horizon. In relation to accepting the message of the New Testament, this article shows how the imago Dei worldview underpins Pauline ethics and can serve as a framework of understanding an anthropological ethical paradigm.Keywords: Imago Dei; Corinthian; Paul